Assessment of Admission COVID-19 Associated Hyperinflammation Syndrome Score in Critically-Ill COVID-19 Patients. (January 2023) - Yildirim, Mehmet; Halacli, Burcin; Yuce, Deniz; Gunegul, Yunus; Ersoy, Ebru Ortac; Topeli, Arzu
Purpose: We aimed to evaluate the relation between admission COVID-19 associated hyperinflammatory syndrome (cHIS) score and intensive care unit (ICU) outcomes. Materials and Methods: Patients with laboratory confirmed COVID-19 admitted to our ICU between 20 th March 2020-15 th June 2021 were included. Patients who received immunomodulatory treatment except corticosteroids were excluded. Main outcomes were ICU mortality and invasive mechanical ventilation (IMV) requirement after ICU admission. Results: Three hundred and seventy patients with a median (IQR) age of 66 (56-77) were analyzed. Median admission cHIS score was 3 (2-4). A cHIS score ≥3 was found to be associated with ICU mortality (sensitivity = 0.63, specificity = 0.50; p < 0.01) and IMV requirement after ICU admission (sensitivity = 0.61, specificity = 0.51; p < 0.01). Patients with an admission cHIS score ≥3 (n = 199) had worse median admission APACHEII, SOFA scores and PaO2 /FiO2 ratio than others (n = 171) (p < 0.01). IMV requirement after ICU admission (38.5% vs 26.1%;p = 0.03), ICU (36.2% vs 25.1%;p = 0.02), hospital (39.1% vs 26.9%;p = 0.01) and 28th day (28.1% vs 19.1%;p = 0.04) mortality were higher in patients with admission cHIS score ≥3 than others (p < 0.01). Age <65 years, malignancy and higher admission SOFA score were independent variables associated with admission cHIS score ≥3. Conclusion: Critically-ill COVID-19 patients with admission cHIS score ≥3 have worse disease severity and outcomes than other patients.